Structural and characterisation analysis of zinc-substituted hydroxyapatite with wet chemical precipitation method - (:unkn) unknown (Inderscience Publishers, 2016)
Hydroxyapatite (HAp) is a biocompatible, bioactive and biodegradable biomaterial widely used in the biomedical area. In this work, the synthesis of zinc substituted hydroxyapatite (Zn-HAp) is described. Zn-Hap nano-powders with 0.5, 2, 5, 10 and 25 wt.% zinc were produced by wet chemical synthesis method. The samples were analysed by XRD for determine crystallite size and phase composition of each sample, SEM and HR-TEM for determine the size and shape of the nanoparticles while FTIR was used to identify the chemical changes of the samples. According to the XRD data, the crystallite size decreased when the increase of the zinc concentration. Therefore, HAp structure was observed in all samples except the sample with 25 wt.% Zn where mostly monetite and parascholzite were obtained instead of HAp. Its structure was deformed and also agglomerated by high zinc-content. Copyright © 2016 Inderscience Enterprises Ltd.
Keywords: Hydroxyapatite; Wet chemical synthesis processing; Zinc substitution